2015
DOI: 10.18280/ijht.330422
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Research on the Transonic Aeroelasticity of a High-Aspect-Ratio Wing

Abstract: A numerical simulation based on CDF/CSD methods is conducted to investigate the transonic static aeroelastic issues of large aircraft. The RANS equation and structural statics equations are utilized as governing equations to do coupling iterative calculation. In order to improve the accuracy and efficiency of CFD, multi-block structured grids are employed for parallel computation and the multi-grid method is used to accelerate convergence. Additionally, a dynamic mesh generation technique, based on a radial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Kilian et al [13] studied the impacts of Reynold number on the flow field in a GT model combustor under atmospheric pressure conditions and found that the frequency of the PVC increases linearly with an increase in the inlet Reynold number of premixed air and methane in non-reacting flow. Similar research conclusions of inlet Reynold number or volumetric flow rate on instability frequency in non-reacting flow also can be found in some other related studies [14]. Furthermore, the occurrence of pressure is relatively more complex in the reacting flow [2].…”
Section: Introductionsupporting
confidence: 85%
“…Kilian et al [13] studied the impacts of Reynold number on the flow field in a GT model combustor under atmospheric pressure conditions and found that the frequency of the PVC increases linearly with an increase in the inlet Reynold number of premixed air and methane in non-reacting flow. Similar research conclusions of inlet Reynold number or volumetric flow rate on instability frequency in non-reacting flow also can be found in some other related studies [14]. Furthermore, the occurrence of pressure is relatively more complex in the reacting flow [2].…”
Section: Introductionsupporting
confidence: 85%
“…The Spalart-Allmaras turbulence model was chosen. The mesh deformation is calculated by using RBF combined with the TFI method [29,30]. The wing surface pressure distribution is solved by the N-S equation, and the structural dynamics equation is obtained:…”
Section: Cfd and Fluid-solid Coupling Calculation Methodsmentioning
confidence: 99%
“…e RBF can be regarded as a three-dimensional extension of the surface spline interpolation method [29]. Its interpolation formula is expressed as…”
Section: Generation Methods For Dynamic Meshmentioning
confidence: 99%